Health Sector Inadequacies in Attending to Child Survivors of Sexual Abuse in Kenya: An Operations Research. (22nd November 2018) - Ajema, Carolyne; Undie, Chi‐Chi; Mbugua, Charity; Kyongo, Jordan; Digolo, Lina
Abstract : In 2015, LVCT Health (a Kenyan non‐governmental organisation) conducted an exploratory study to assess the quality and comprehensiveness of services provided to child survivors of sexual violence at two public health facilities in Kenya. Both quantitative and qualitative data collection methods were used, including a retrospective review of 164 child survivor medical records, a health facility staff inventory, in‐depth interviews with 31 healthcare providers and 19 exit interviews with 14 child survivors and their caregivers. Ethical approval was obtained from two independent ethics committees. Quantitative data were analysed using SPSS version 22, while qualitative data were analysed using NVivo 10 based on a thematic coding framework. The health facility staff inventory indicated that only two out of 581 providers had undergone previous training on the management of child survivors of sexual violence. Both health facilities lacked the appropriate equipment for the collection of forensic evidence from children and private rooms in which to conduct the clinical examination. Providers cited challenges in offering psychosocial support to children. Only 27 per cent of child survivors were documented to have received trauma counselling. There is a need for health facilities to enhance their human resource and infrastructural capacity to facilitate the delivery of comprehensive care to child survivors. 'An exploratory study to assess the quality and comprehensiveness of services provided to child survivors of sexual violence… in Kenya' Key Practitioner Messages: There is a need to develop child‐specific guidelines for healthcare providers in order to ensure that child survivors of sexual violence receive good‐quality services at the facility level. Healthcare providers in public health facilities need competency‐based training to enable them to acquire knowledge and skills to identify and respond to child survivors of sexual violence, collect evidence, communicate with the children and offer counselling support to child survivors effectively. Services for child survivors should be centralised in health facilities to minimise the number of different contact points.